Trilobatin Protects Against Oxidative Injury in Neuronal PC12 Cells Through Regulating Mitochondrial ROS Homeostasis Mediated by AMPK/Nrf2/Sirt3 Signaling Pathway - Gao, Jianmei; Liu, Shuang; Xu, Fan; Liu, Yuangui; Lv, Chun; Deng, Yan; Shi, Jingshan; Gong, Qihai (Frontiers in Molecular Neuroscience, 2018)
Oxidative stress-induced neuronal cell damage is a crucial factor in the pathogenesis of mitochondria-associated neurological diseases. Therefore, elimination of overproduction of mitochondrial ROS (mtROS) may be a potential strategy for prevention and treatment of neurological diseases. In the present study, the neuroprotective effects of trilobatin (TLB), a novel small molecule monomer derived from Lithocarpus polystachyus Rehd, and its underlying mechanisms were investigated in vitro using hydrogen peroxide (H2O2)-induced oxidative stress model in a neuron-like PC12 cell. The findings revealed that pre-treatment with TLB dramatically concentration-dependently suppressed H2O2-induced PC12 cells damage by enhancing cell viability, repressed reduction of mitochondrial membrane potential and decreased mtROS overgeneration, thereby deferring cell apoptosis. Further study demonstrated that TLB not only increased the enzymatic activities of GPx, IDH2, SOD2 and deacetylation of SOD2, but also activated Sirt3 within the mitochondria and thereby upregulating FoxO3a, which regulated mitochondrial DNA genes, then led to improving complex I activity and ATP synthesis. What’s more, TLB up-regulated p-AMPK level, the expression of PGC-1α, and ERRα. Intriguingly, TLB failed to mitigate H2O2-induced PC12 injury in the presence of the AMPK inhibitor (Compound C), indicating that the beneficial effects of TLB on the regulation of mtROS homeostasis were reliance on AMPK -Sirt3 signaling pathway. Moreover, TLB also facilitated Nrf2 and promoted antioxidant gene expression in turn, and knockdown of Nrf2 by siRNA dramatically reduced the neuroprotective effects of TLB. Notably, AMPK inhibitor abolished the activation of Nrf2 and Sirt3, whereas, knockdown of Nrf2 blocked the upregulation of Sirt3, but it did not affect p-AMPK level. In conclusion, our findings demonstrate that TLB protects against oxidative injury in neuronal PC12 cells through regulating mtROS homeostasis in the first time, which is, at least partly, mediated through the AMPK/Nrf2/Sirt3 signaling pathway.